NURSE NEED MANAGEMENT DURING COVID 19 PANDEMIC - Patimah; Sri Eka Wardani; ilhamsyah ilhamsyah (Homes Journal = Hospital Management Studies Journal, 2022)
Background: Currently, coronavirus disease (COVID-19) is a major problem throughout the world. World Health Organization (WHO) has declared COVID-19 a global health emergency. The purpose of writing this scientific paper is to identify the needs of nurses during the COVID-19 pandemic. Method: This study uses a qualitative descriptive with a literature review approach. Results: The results of a literature study of 423 articles obtained only 10 articles that met the inclusion criteria. The results of the study show that nurses are a large proportion of staff in hospitals, it is estimated that around 75% of personnel are nurses. As the number of COVID-19 continues to increase, hospitals are faced with a shortage of health workers, especially nurses, to treat COVID-19 patients. Conclusion: Results showed that 74% of nurses favored the third schedule for the following reasons: wearing and removing PPE twice a day increased the consumption of medical resources, frequent switching between contaminated and clean areas increased the risk of infection, frequent complicated procedures wearing and removing PPE increased the risk of infection. their mental burden, working for 6 hours continuously pushes their physiological limits, because they cannot go to the bathroom when wearing PPE in isolation area.